Health and safety in the gig economy: a qualitative investigation with TaskRabbit workers - Kaldahl, Kiplin, author; Fisher, Gwenith G., advisor; Crain, Tori L., committee member; Rosecrance, John, committee member; Harman, Jennifer, committee member (Colorado State University. Libraries, 2020)
Work in the United States is increasingly moving towards contingent positions in the online gig economy, raising concerns about worker health, safety, and well-being in the absence of regulatory frameworks found in traditional employment. The present study examines the health and safety experiences of workers who provide their labor through an online platform called TaskRabbit, which is characterized by gig economy workers who offer freelance labor services to clients, such as cleaning and moving services. Little research has been done with this population; most studies on gig economy workers thus far have focused on on-demand driving companies such as Uber and Lyft. Health risks may arise from little workplace support for physical and mental health. Safety hazards may arise from a lack of training, unregulated physical environments in which tasks take place, and risk of injury due to physical labor. Negative outcomes due to stress may arise from low job control due to algorithmic management (i.e., computerized algorithms that make management decisions based on statistics such as customer approval ratings), and from interpersonal stressors such as incivility (i.e., rude comments, inconsiderate behavior) and unfair treatment. I investigated these potential risks through the use of one-hour, semi-structured qualitative interviews conducted via online video. The interview data was analyzed for recurring themes and sub-themes related to the study topics. The findings provide information on the unique health and safety experiences of the TaskRabbit workforce, which is essential to the development of future quantitative studies and interventions.
Keywords: health; safety; TaskRabbit; qualitative; gig economy; stress